THE EXPERIENCE OF PEDIATRIC HEART TRANSPLANTATION ON NORTH-WEST OF RUSSIAN FEDERATION - M. A. Simonenko; T. M. Pervunina; P. A. Fedotov; Yu. V. Sazonova; E. S. Vasichkina; V. E. Rubinchik; A. V. Berezina; D. A. Zverev; A. E. Bautin; A. A. Kostareva; A. P. Polyakova; L. B. Mitrofanova; et al. (Вестник трансплантологии и искусственных органов)
Aim: to estimate early and long-term outcomes in recipients under 18 years old who have been heart transplanted in Almazov National Medical Research Centre. Materials and methods. From April 2011 to September 2017 we performed 5 heart transplantations (HTx) in recipients under 18 years old (female) old) from adults donors. The median of age were 15 years (range 10–16 years), LVEF prior HTx – 17% (10–33%). Causes of heart failure were dilated cardiomyopathy (n = 2), non-compacted myocardium (n = 1), arrhythmogenic ventricular dysplasia (n = 1) and Ebstein’s anomaly (n = 1). They spent in HT waiting list 76 days (12–684 days). One patient underwent biventricular assist device Berlin Heart EXCOR implantation (days on support – 250) as a «bridge» to transplant. Due to coronary angiography (CAG) results 1 patient underwent HTx and CABG simultaneously. All recipients treated by triple-drug therapy (steroids, calcineurin inhibitors, mycophenolate mofetil), induction (thymoglobulin – n = 4, basiliximab – n = 1). We evaluated retrospectively laboratory-instrumental investigations and frequency of complications after HTx.Results. The median of survival after HT was 35,93 months (4,4–73,7 months), all of them are alive. Patients spent in ICU 12 days (4–18 days), but one – 18 days due to posterior reversible encephalopathy syndrome (PRES), tacrolimus was switched to cyclosporine. They required inotropic support during 3 days (3–8 days). In 1 yr after HT TTE results got to normal values, the same as VO2peak signiﬁ cantly improved. According to EMB (n = 48) results there were no clinical signs of rejection, acute cellular rejection (R2) was diagnosed in 12,5% cases. In long-term follow-up there was no signiﬁ cant post transplant complications and comorbidities.Conclusion. Pediatric heart transplantation is an effective treatment of terminal CHF. There was no signiﬁ cant clinical rejection under combined immunosuppressive regimens. All patients recovered and went back to normal life. Physical capacity improved in all recipients.